SISTEM REKOMENDASI PRODUK DENGAN DATA MINING METODE FUZZY C-MEANS UNTUK MENDUKUNG STRATEGI PENJUALAN PRODUK PADA INDUSTRI KREATIF - Yorda Tri Wardhana Virbiyasa, - (2019)
PT. INFIA NIAGA DIGITAL is a company engaged in the field of media and advertising that is very well known among millennials, especially on Instagram social media besides selling a product, this company also gives us new information and viral on social media. Industry 4.0 is a relatively new term and may still not be widely known and understood by audiences in the industrial field. In the opinion of the Minister of Industry and Trade (Work Cabinet) Airlangga Hartarto quoted from Glienmourinsie (2016), Industry 4.0 made the production process run with the internet as the main support. Data Mining is a process that uses statistical techniques, mathematics, artificial intelligence, machine learning to extract and identify useful information and related knowledge from various large databases. Fuzzy clustering is the process of determining the degree of membership, and then using it by entering it into data elements into one or more cluster groups.